Dare to Ask! A Model for Teaching Nursing Students about Identifying and Responding to Violence against Women and Domestic Violence - Leah Okenwa Emegwa; Stéphanie Paillard-Borg; Inger Wallin Lundell; Anna Stålberg; Maria Åling; Gabriella Ahlenius; Henrik Eriksson (Nursing Reports, 2024)
The role of nurses in identifying and responding to family violence and violence against women has long been established. However, nurses’ readiness to fully assume this role remains low due to various barriers and the sensitive nature of the subject. As part of capacity building to address this problem, an additional national qualitative learning target, i.e., to “show knowledge about men’s violence against women and violence in close relationships”, was introduced into the Swedish Higher Education Ordinance for nursing and seven other educational programs between 2017 and 2018. The aim of this paper is to describe how the national qualitative learning target is incorporated into the undergraduate nursing curriculum at the Swedish Red Cross University College. An overview of relevant teaching and learning activities and how they are organized is first presented, followed by the presentation of a proposed didactic model: Dare to Ask and Act! The model details a step-by-step progression from facts and figures, including the role of gender norms, to recognizing signs of abuse in complex clinical situations, as well as developing skills that enhance the courage to ask and act. Due to the sensitive nature of violence victimization, the proposed model reflects the importance of making the subject a reoccurring theme in undergraduate nursing education in order to boost nursing students’ interests and confidence to “Dare to Ask and Act!”. The model also shows that making the subject a recurring theme can be achieved with minimal disruptions to and without overcrowding an existing curriculum.